2021
DOI: 10.3390/app11031283
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Driving Altitude and Ambient Temperature Impact on the Conversion Efficiency of Oxidation Catalysts

Abstract: Worldwide emission standards are extending their requirements to cover engine operation under extreme ambient conditions and fill the gap between the type-approval and real driving conditions. The new ambient boundaries affect the engine performance and raw emissions as well as the efficiency of the exhaust aftertreatment systems. This study evaluates the impact of high altitude and low ambient temperature on the light-off temperature and conversion efficiency of an oxidation catalyst. The results are compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…This was the case with the highest sensitivity due to the temperature range ( 190 210 ° C) around the light-off temperature. 17 This behaviour was also found in cold altitude operation. In this case, the residence time of the gas within the catalyst increased due to the lower boost pressure (lower exhaust mass flow) and the temperature moved to a higher range from 195°C to ~ 220 ° C (Figure 4).…”
Section: Pollutant Emissionsmentioning
confidence: 53%
See 1 more Smart Citation
“…This was the case with the highest sensitivity due to the temperature range ( 190 210 ° C) around the light-off temperature. 17 This behaviour was also found in cold altitude operation. In this case, the residence time of the gas within the catalyst increased due to the lower boost pressure (lower exhaust mass flow) and the temperature moved to a higher range from 195°C to ~ 220 ° C (Figure 4).…”
Section: Pollutant Emissionsmentioning
confidence: 53%
“…As ambient temperature, the altitude variation, which implies different ambient pressures, also leads to relevant effects on the combustion, 14 the gas exchange processes 15 and the ATS performance 16,17 . Wang et al 18 found a progressive decrease in brake thermal efficiency with increasing altitude in a heavy duty diesel engine.…”
Section: Introductionmentioning
confidence: 99%
“…The initial phase of the study was based on tests conducted by Serrano et al [16] on an HSDI diesel Euro 6d-Temp engine installed in a test bench coupled with the Horiba MEDAS. The MEDAS system, an altitude simulator developed by CMT -Thermofluids & Clean Mobility [29,30], facilitated variable working pressure for the engine based on the designated driving altitude.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental facility used as a base to conduct the first part of the study consisted of an HSDI diesel Euro 6d-Temp engine for passenger car application, whose detailed characteristics are described in [16]. The engine was installed in a test bench integrated with Horiba MEDAS which can handle altitudes from sea level to 5000 m and ambient temperatures from -15 to 45 • C [29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation